Educational Philosophy for 21st Century Teachers - Stehlik, Thomas (Springer International Publishing, 2018)
This book explores education in the 21st century in post-modern Western societies through a philosophical lens. Taking a broad perspective of education and its attendant terminology, assumptions, myths and influences; the author examines why we teach as opposed to how. In doing so, he includes not only teachers, but all adults who are involved in bringing up children. Applying philosophical theories throughout history to present day practice, this volume is sure to be a useful resource not only for teachers who are just starting out, but those with an interest in education in the past, present and future. This wide-ranging book will be valuable for educators, parents and educational policy makers, and all those who believe it takes a village to raise a child.